Optimalisasi Pemanfaatan Tanaman Penjernih Udara di Lingkungan SMA/SMK/Sederajat Kecamatan Rengel dan Plumpang Kabupaten Tuban Jawa Timur - Kuntum Febriyantiningrum; Dwi Oktafitria; Nia Nurfitria (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2019)
‘The purpose of this community service program is to help and enhance environmental conservation efforts that are more effective, efficient, and targeted for schools in the karst region in creating a healthy environment free of air pollution. The problem faced by partners is the lack of school participation in the karst area to deal with the increasing dust volume in the dry season which can disrupt teaching and learning activities. Low school participation is due to a lack of student and teacher knowledge about air-purifying plants that can be planted in the school environment. The solution offered to school partners as a first step is to hold a workshop to introduce karst areas and plant species that are useful as air purifiers. The implementation of the workshops that have been carried out can increase the understanding of students and teachers about the condition of the school environment, types of air purification plants, and the use of used materials for growing media. The monitoring results show that the partner schools namely SMAN 1 Plumpang and SMAN 1 Rengel have implemented the results of the workshop, namely by planting various air purification plants by utilizing used materials as planting media so as to achieve a beautiful environment and environmental conservation in the karst school area running well.